2013
DOI: 10.6090/jarq.47.353
|View full text |Cite
|
Sign up to set email alerts
|

Potential Utilization of Local Phosphate Rocks to Enhance Rice Production in Sub-Saharan Africa

Abstract: It is known that phosphate rock (PR) deposits that account for most world's PR production are found in African countries. However, the rate of phosphorus (P) fertilizer use in Africa is typically low, despite the high requirement for application of the same there. This applies particularly to sub-Saharan Africa (SSA), where P deficiency has been suggested as one of the key constraints to crop production, despite the many PR deposits. There have been many excellent reviews on PR utilization in SSA, but hardly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…A vast amount of geological phosphate rock (PR) deposits has been found throughout SSA (10). According to the Burkina Faso Government, there are 100 million metric tons of PR in the Kodjari region of Burkina Faso (11), which could serve as an alternative source of P fertilizer (12). However, most of these have not been utilized because of their low solubility and reactivity (13).…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of geological phosphate rock (PR) deposits has been found throughout SSA (10). According to the Burkina Faso Government, there are 100 million metric tons of PR in the Kodjari region of Burkina Faso (11), which could serve as an alternative source of P fertilizer (12). However, most of these have not been utilized because of their low solubility and reactivity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would be very desirable, if not necessary, to enhance fertilizer use in much of Africa. The development of low-cost technologies for alleviating P deficiency, such as direct use of low-grade phosphate rock in conjunction with organic resources (Nakamura et al 2013 ; Appleton 2002 ) could offer a sustainable solution.…”
Section: Introductionmentioning
confidence: 99%
“…The applied phosphate rock in these three treatments may have been gradually solubilized but absorbed poorly by sorghum roots, probably due to environmental factors such as soil concretion and limited soil moisture, justifying the lower yields obtained in these treatments compared to P-Comp-Soil and NPK. The sub-Saharan African PRs effectively achieved high performance in lowland rice, following direct application (Nakamura et al 2013). We did not obtain a similar result in the present study on upland sorghum cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate rock (PR), an essential material existing in large deposits in several African countries, including Burkina Faso, is included in soil fertilization strategies via a direct application or is added to composts during the composting process to improve the compost phosphorus content. Nakamura et al (2013) found that sub-Saharan African PRs effectively achieve high performance in lowland rice, following direct application, regardless of the PR reactivity and the location investigated. However, under water-limited conditions such as upland cultivation of rice or other crops, the effects of the initial PR direct application may be depressed, although it may enhance the total P of soil and have a residual effect in subsequent cultivations (Nakamura et al 2016;Nakamura et al 2020).…”
Section: Introductionmentioning
confidence: 91%